ANALYSIS OF THE GALODO FLOOD DISASTER FROM YEAR 1979 AND YEAR 2009 PASIE LAWEH, BATUSANGKAR - Kevin Eduardo (Pendidikan IPA, FMIPA, UNP, 2020)
The purpose of this paper is to analyze the flash floods from 1979 and 2009 to explore local wisdom in the community related to the science of natural events (Galodo). This observation activity was carried out by the Galodo incident in Pasie Laweh, Sungi Tarab, Tanah Datar. Negeri Pasie Laweh (Pasla) is a beautiful village located at the foot and slopes of Mount Merapi, one of the highest mountains in West Sumatra Province. Cool air, beautiful and seductive scenery, and residents who always adhere to the philosophy of